Proceedings of the 3d International ICST Conference on Pervasive Computing Technologies for Healthcare 2009
DOI: 10.4108/icst.pervasivehealth2009.6069
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational communication systems in support for elder adults with cognitive decline

Abstract: Cognitive decline diseases, such as dementia, could be prevented through Cognitive Stimulation (CS) activities in which elders' relatives participate as informal caregivers. We carried out case studies for understanding the role of technology in the evolution of the relationships among older adults and their children, and the practices, roles and responsibilities of the elders' relatives in a CS session. Based on the results for these case studies we are proposing a pervasive system that incorporates mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The areas of attention less frequently addressed are research (6%, 1/16) and diagnosis (6%, 1/16). It is important to point out that the studies indicated in references [ 38 , 39 ] are projects previously developed in Mexico. These studies are important because there is little evidence of these types of projects in Mexico, to our knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…The areas of attention less frequently addressed are research (6%, 1/16) and diagnosis (6%, 1/16). It is important to point out that the studies indicated in references [ 38 , 39 ] are projects previously developed in Mexico. These studies are important because there is little evidence of these types of projects in Mexico, to our knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, a few of the care applications we have reviewed have an impact on other determinants including psychological factors, social support and risk of violence and abuse. When addressing psychological factors, the goal is either on facilitating family involvement on cognitive training [Meza-Kubo et al 2009] (which in turns increases social support) or on facilitating the task of remotely following and assisting daily life activities [Gorman et al 2003] of patients with cognitive disabilities. More evaluation, however, is needed to establish the effectiveness of these applications.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, only one IT for care contribution in our review falls well under the category of social applications, improving the social support determinant through a cognitive training platform where caregivers can assist patients with cognitive impairment in cognitive tasks that are part of training program [Meza-Kubo et al 2009]. Although this application can be also classified as a training application that addresses psychological factors, the focus of the contribution is set on the platform to involves the family network in assisting the cognitive training from remote, putting the social aspect upfront.…”
Section: Applications For Carementioning
confidence: 99%
“…Finally, only one IT for care contribution in our review falls well under the category of social applications, improving the social support determinant through a cognitive training platform where caregivers can assist patients with cognitive impairment in cognitive tasks that are part of training program [116]. Although this application can be also classified as a training application that addresses psychological factors, the focus of the contribution is set on the platform to involves the family network in assisting the cognitive training from remote, putting the social aspect upfront.…”
Section: Applications For Carementioning
confidence: 99%
“…In contrast, a few of the care applications we have reviewed have an impact on other determinants including psychological factors, social support and risk of violence and abuse. When addressing psychological factors, the goal is either on facilitating family involvement on cognitive training [116] (which in turns increases social support) or on facilitating the task of remotely following and assisting daily life activities [64] of patients with cognitive disabilities. More evaluation, however, is needed to establish the effectiveness of these applications.…”
Section: Characterisitics Of It For Carementioning
confidence: 99%